Still life : still life painting in the early modern period - Schneider, Norbert, 1945-; Taschen (Firm) (Koln : Taschen, 2009)
This title presents a reflection of the customs, ideas, and aspirations of the time via still lifes. The still life, the most primordial of painting subjects, had its peak between the late Middle Ages and the 17th century. In this book, Norbert Schneider explores the still life's insights into changes of mentality and philosophy as well as its role in the history of scientific discoveries and the gradual replacement of the medieval concept of the world.
Art and Artists.
Originally published: 1990.
Includes bibliographical references.
Translated from the German.
Keywords: Still-life painting; Still-life painting, European -- 16th century; Still-life painting, European -- 17th century